Differences in outcome after cruciate retaining and posterior stabilized total knee arthroplasty. (17th May 2019) - Singleton, Neal; Nicholas, Bryden; Gormack, Nick; Stokes, Andrew
Background: Both cruciate retaining (CR) and posterior stabilized (PS) implants are commonly used for primary total knee arthroplasty. There is evidence to support improved range of motion in PS knee replacements, but there is no evidence showing functional superiority. The aim of this study was to compare functional outcomes between CR and PS knee replacements. Patient and methods: Prospectively collected regional joint registry data were used to compare preoperative and postoperative one, 5- and 10-year Oxford and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores in 1287 primary total knee replacements. Differences in functional scores between CR and PS knees were calculated. Results: The PS group had better functional scores than the CR group at baseline (mean Oxford score 15.59 vs. 14.52 ( p = 0.026) and mean WOMAC score 59.51 vs. 62.35 ( p = 0.012)), at 1 year postoperatively (mean Oxford score 37.94 vs. 36.63 ( p = 0.015) and mean WOMAC score 16.20 vs. 19.73 ( p = 0.001)) with a similar trend at 5 years postoperatively (mean Oxford score 39.66 vs. 38.50 ( p = 0.054) and mean WOMAC score 16.89 vs. 18.83 ( p = 0.131)). There was no difference in the overall functional improvement between the PS and CR groups at 1, 5, or 10 years. WOMAC subcomponent scores showed greater improvement in stiffness; 3.76 versus 3.36 ( p = 0.012) in PS knees at 1 year postoperatively. No significant differences were observed at 5 or 10 years. Conclusions: PS knee replacements showed greater improvement in stiffness at 1 year postoperatively. There was no difference observed at 5 or 10 years postoperatively. PS knees had better functional outcomes at 1 year with a similar trend at 5 years postoperatively. Level of evidence: III.